2016
DOI: 10.1039/c6cc00895j
|View full text |Cite
|
Sign up to set email alerts
|

[11C]Ascorbic and [11C]dehydroascorbic acid, an endogenous redox pair for sensing reactive oxygen species using positron emission tomography

Abstract: Here we report the radiosynthesis of an endogenous redox pair, [11C]ascorbic acid ([11C]VitC) and [11C]dehydroascorbic acid ([11C]DHA), the reduced and oxidized forms of vitamin C, and their application to ROS sensing. These results provide the basis for in vivo detection of ROS using positron emission tomography (PET).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 53 publications
3
48
0
3
Order By: Relevance
“…Currently a standardized range for oxidation status within cancer cells does not exist, therefore normal surrounding tissue can be used as a comparative control. New PET imaging technologies are emerging that may help facilitate ROS measurement without biopsies …”
Section: Conclusion and Treatment Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently a standardized range for oxidation status within cancer cells does not exist, therefore normal surrounding tissue can be used as a comparative control. New PET imaging technologies are emerging that may help facilitate ROS measurement without biopsies …”
Section: Conclusion and Treatment Implicationsmentioning
confidence: 99%
“…New PET imaging technologies are emerging that may help facilitate ROS measurement without biopsies. 119,120 If baseline ROS status is low, treatment with an antioxidant may further deplete the cancer of necessary ROS signaling. Knowing if cells have higher baseline ROS levels can be helpful in anticipating responsiveness to ROSinducing therapy.…”
Section: Conclusion and Treatment Implicationsmentioning
confidence: 99%
“…Molecular imaging of ROS/RNS is an emerging area of research in redox and free radical biology [68]. Bioluminescence or fluorescence modalities are typically used.…”
Section: Introductionmentioning
confidence: 99%
“…The first synthesis of 18 F-Vitamin C was accomplished with 18 F incorporated at the 6-position by Kothari et al, generating a molecule incapable of forming a bicyclic species due to the substitution of 18 F for a hydroxyl group(25,26). Recently, a synthesis of 11 C Vitamin C was reported, for which the authors reported accumulation of 11 C in ROS-producing cells via ascorbate recycling(27). The presumed mechanism of 11 C ascorbate recycling is shown in Figure 4.…”
Section: Why 11c?mentioning
confidence: 99%
“…Dysregulation of reactive oxygen species (ROS) provides a powerful motivation to develop non-invasive biomarkers of oxidative stress. A synthesis of 11 C Vitamin C was recently reported, synthesized from 11 C cyanide and L-xylosone based on a modification of the previously reported 13 C and 14 C enrichment techniques(27). The authors studied sensitivity to numerous inflammation-relevant ROS including H 2 O 2 , superoxide, and hypohlorite, and showed ROS-dependent accumulation in activated neutrophils.…”
Section: Reduction and Oxidation- Vitamin C And Uric Acidmentioning
confidence: 99%